Left ventricular biomechanics in professional football players - von Lueder, T. G.; Hodt, A.; Gjerdalen, G. F.; Steine, K. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Chronic exercise induces adaptive changes of left ventricular (LV) ejection and filling capacities which may be detected by novel speckle-tracking echocardiography (STE) and tissue Doppler imaging (TDI)-based techniques.